Violence Eradication in Education through a Juridical-Religious Approach: Seeking an Ideal Model under the Criminal Justice System - Fatoni, Syamsul (Al-Risalah, 2020)
Violence in education has led to criminal activities that require special attention from all parties. This paper discusses preventive measures of violence in education through a juridical-religious approach under the criminal justice system. This paper is a doctrinal law study in which an analysis of legal materials is used to answer legal problems and produce legal arguments. This paper demonstrates that the incorporation and operation of these two approaches under the criminal justice system will be very effective and useful for preventing and controlling crimes in schools because, first, the juridical approach can prevent students from becoming victims of violence and educate them not to repeat the same crimes; secondly, the religious approach will instill a faithful, pious character and noble personality into students so that they avoid crimes.